Un nuevo registro de Cyperus para México - Diego-Pérez, Nelly; Ramos Álvarez, Clara Hilda; Martínez, Esteban (Instituto de Ecología, A.C., 2001)
Cyperus gardneri Nees is reported for the first time for the flora of Mexico and some additional data on its distribution are included.